Meat consumption and flexitarianism in the Low Countries. (October 2022) - Dagevos, Hans; Verbeke, Wim
Abstract: Against the backdrop of meat production and consumption being increasingly contested, this paper presents a narrative descriptive review of (reductions in) meat consumption in the Netherlands and Belgium with a focus on trends during the period 2010–2020. Based on household panel purchasing data and supply balance sheet data as proxies, our analysis shows that meat consumption in the Netherlands is relatively stable, based on supply balance sheet data, despite an estimated annual decrease of around 250 g per capita per year based on household panel purchasing data. Meanwhile, household purchasing panel data for Belgium show a more steady and stronger decline with an annual decrease of slightly >1 kg per capita per year over the past decade, as well as more fluctuations based on supply balance sheet data. The 'Covid-year' 2020 displays a distinct pattern in both countries which deserves further exploration. Both countries face growing shares of (self-declared) flexitarians (ranging from around or above 30% in Belgium to 40% or more in the Netherlands depending on the data source and its definition of flexitarians) and consumers who claim to intend reducing their meat consumption in the future. The analysis reveals important differences in research methodologies, sample compositions, and analytical techniques. Such differences raise caveats for direct comparison between countries and impose challenges for the (European) monitoring of the so-called 'protein transition'. Although some change is occurring, the data suggest that meat reduction calls resonate still more in terms of people's attitudes, awareness, and intentions than in overt dietary behavioral change. Overall, our findings provide reason to conclude that the established meat-centered food system and its dominant meat-eating culture are still prevailing in the Low Countries.